Liquidity risk in securities settlement - Johan Devriese; Janet Mitchell (National Bank of Belgium, 2005)
This paper studies the potential impact on securities settlement systems (SSSs) of a major market disruption, caused by the default of the largest player. A multiperiod, multisecurity model with intraday credit is used to simulate direct and second-round settlement failures triggered by the default, as well as the dynamics of settlement failures, arising from a lag in settlement relative to the date of trades. The effects of the defaulter's net trade position, the numbers of securities and participants in the market, and participants' trading behavior are also analyzed. We show that in SSSs - contrary to payment systems - large and persistent settlement failures are possible even when ample liquidity is provided. Central bank liquidity support to SSSs thus cannot eliminate settlement failures due to major market disruptions. This is due to the fact that securities transactions involve a cash leg and a securities leg, and liquidity can affect only the cash side of a transaction. Whereas a broad program of securities borrowing and lending might help, it is precisely during periods of market disruption that participants will be least willing to lend securities. Settlement failures can continue to occur beyond the period corresponding to the lag in settlement. This is due to the fact that, upon observation of a default, market participants must form expectations about the impact of the default, and these expectations affect current trading behavior. If, ex post, fewer of the previous trades settle than expected, new settlement failures will occur. This result has interesting implications for financial stability. On the one hand, conservative reactions by market participants to a default - for example by limiting the volume of trades - can result in a more rapid return of the settlement system to a normal level of efficiency. On the other hand, limitation of trading by market participants can reduce market liquidity, which may have a negative impact on financial stability.
Keywords: G20; G28; 330; Securities settlement; liquity risk; contagion; Clearing; Wertpapierhandel; Bankenliquidität; Simulation